2020
DOI: 10.1021/acs.accounts.0c00212
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Ionic Interactions at Protein–Nucleic Acid Interfaces

Abstract: Conspectus Molecular association of proteins with nucleic acids is required for many biological processes essential to life. Electrostatic interactions via ion pairs (salt bridges) of nucleic acid phosphates and protein side chains are crucial for proteins to bind to DNA or RNA. Counterions around the macromolecules are also key constituents for the thermodynamics of protein–nucleic acid association. Until recently, there had been only a limited amount of experiment-based information about how io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 90 publications
(209 reference statements)
0
47
0
Order By: Relevance
“…This protein is a DNA-binding protein that recognizes the TAATGG sequence. Charge neutralization upon protein-DNA association is known to cause a release of cations from DNA ( 25 27 ). In our recent NMR study using 15 NH 4 + ions, we showed that the 15-bp DNA duplex containing the Antp recognition sequence releases 10.8 cations when it forms a complex with the Antp homeodomain ( 28 ).…”
Section: Resultsmentioning
confidence: 99%
“…This protein is a DNA-binding protein that recognizes the TAATGG sequence. Charge neutralization upon protein-DNA association is known to cause a release of cations from DNA ( 25 27 ). In our recent NMR study using 15 NH 4 + ions, we showed that the 15-bp DNA duplex containing the Antp recognition sequence releases 10.8 cations when it forms a complex with the Antp homeodomain ( 28 ).…”
Section: Resultsmentioning
confidence: 99%
“…The final transfection ability of the mutants appeared to be a sum of the mutations to the protein, demonstrating a “less is more” principle in the design process since seemingly synergistic mutations could actually compete against each other and not yield the desired result. Future designs should aim to further improve protein secondary structure to create even more favorable protein-siRNA interactions [30], while maintaining a favorable positive charge density [31].…”
Section: Discussionmentioning
confidence: 99%
“…In nature, the majority of nucleic acid binding proteins are alphahelical and positively charged [28, 29]. This can allow for sequence specific interactions through the orientation of side chains able to form hydrogen bonds with specific nucleic acid base pairs [30], or sequence independent interactions through electrostatic interactions between positively charged amino acids and the negatively charged nucleic acid phosphate backbone [31]. The degree of alpha-helicity is also important, as more organized alpha-helices have been shown to form more energetically favorable interactions with nucleic acid binding partners [32].…”
Section: Introductionmentioning
confidence: 99%
“…The protein molecule must transiently break all of these ions pairs when it moves from one site to another on DNA. The requirement of breaking all ion pairs could represent an energy barrier for sliding [ 70 ]. In fact, for many proteins, the 1D diffusion coefficient for the sliding on DNA is ~10 2 –10 3 fold smaller than the 3D diffusion coefficient calculated with the Stokes-Einstein equation that gives the diffusion coefficient as a function of the hydrodynamic radius, viscosity, and temperature.…”
Section: Discrete-state Stochastic Kinetic Models For Protein Translomentioning
confidence: 99%
“…Because electrostatic interactions are crucial for protein-DNA association [ 70 ], the kinetics and thermodynamics of protein-DNA interactions strongly depend on the salt concentration used in experiments [ 29 , 34 , 64 , 67 , 83 – 88 ]. The counterion condensation theory predicts a linear relationship between log K d and log[salt] for the dissociation constants of protein-DNA complexes [ 85 , 86 ] and a similar linear relationship between log k and log[salt] for some kinetic rate constants relevant to protein-DNA constants [ 89 ].…”
Section: Experimental Applicationsmentioning
confidence: 99%